The digital (il)literacy of local and regional politicians and civil servants –An analysis based on recent data from Romania - Robert MÜLLER-TÖRÖK; Alexander PROSSER; Sven SROKA (Smart Cities and Regional Development Journal)
In 2021/2022 a consortium of European universities delivered a scientific basis for a policy fighting fake news and hate speech with support of the Congress of Local and Regional Authorities of the Council of Europe, describing also the technical and legal basics of both phenomena. In this context a survey was performed with the delegates of the Congress and the book, which contained also the survey results, was presented to the Congress in its Spring Session 2022. In 2023 a broader survey was done in a selection of countries, which also returned 675 filled-in questionnaires from Romania. The part of the questionnaire dealing with possible remedies contained questions which remedies are considered technically and legally feasible by the participants. Confirming the results of the survey in 2021/2022 the results for Romania showed a severe lack of basic knowledge about how the internet works and its governance. In this paper we want to show the results for Romania in detail, discuss them and suggest possible training measures which seem necessary to make the local and regional politics and administration fit for the Digitalization.The analysis of data from other European countries showed that this phenomenon is not restricted to Romania but is widely recognizable all over Europe. It also confirms the results from the survey among the Congress delegates. Therefore, this paper may be based on the Romanian dataset, however it signifies a pan-European issue.The authors are grateful to Vice Dean  Nicolae Urs (Babeș-Bolyai University Cluj-Napoca) and Catalin Vrabie (National University of Political Studies and Public Administration) for their support in spreading the survey among Romanian municipalities.